2011
DOI: 10.1111/j.1744-313x.2011.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Mannose‐binding lectin and MBL‐associated serine protease‐2 gene polymorphisms in a Brazilian population from Rio de Janeiro

Abstract: Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
9
1
1
Order By: Relevance
“…Although MBL2 gene polymorphisms were not evaluated in healthy subjects, the present data showed similar allele and genotype frequencies in CLL patients as healthy donors from other studies 26., 27.. Regarding MBL2 gene polymorphisms in respect to occurrence of infections, it was not possible to demonstrate a significant association between polymorphisms of the - 221 and - 550 promoter regions and exon 1 of the MBL2 gene with higher risk of infection in CLL patients.…”
Section: Discussioncontrasting
confidence: 49%
“…Although MBL2 gene polymorphisms were not evaluated in healthy subjects, the present data showed similar allele and genotype frequencies in CLL patients as healthy donors from other studies 26., 27.. Regarding MBL2 gene polymorphisms in respect to occurrence of infections, it was not possible to demonstrate a significant association between polymorphisms of the - 221 and - 550 promoter regions and exon 1 of the MBL2 gene with higher risk of infection in CLL patients.…”
Section: Discussioncontrasting
confidence: 49%
“…Signi cant differences in the distribution of MBL2 and FCN3 alleles and genotypes have been identi ed among the population from various continents. These distinctive genetic patterns may almost certainly affect serum MBL and colin-3 levels, accordingly modifying worldwide susceptibility for the disease [60,61]. What's more, the presence of the C allele in controls in highly signi cant patterns as compared to RF patients could show that the presence of the C allele may have a defensive action against the occurrence of RF and RHD.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed significantly different distribution of MBL2 and FCN2 alleles, genotypes and haplotypes among populations from different continents. These different genetic patterns may likely contribute to altered serum ficolin-2 and MBL levels, thus modulating disease susceptibility among world populations [35, 36].…”
Section: Discussionmentioning
confidence: 99%